Efecto de la asociación de fipronil 1% e ivermectina 0.5% vía epicutánea sobre el control de garrapatas boophilus microplus en bovinos. - Alvarez Zambrano, Mario David (2017)
This research project has as a principla study the efficacy of a formulation based on 1% fipronil and ivermectin 0.5% epicutaneous application on the control of Boophilus microplus ticks in cattle at the Jeiyukeda farm, located El Carmen Cantón of Manabí in Ecuador, Six different doses were evaluated (T2: 0.5ml / 10kg / pv, T3: 1ml / 10kg / pv, T4: 1.5ml / 10kg / pv) were used and 16 as T1 control: 1% fipronil, 1ml / 10kg / pv. In order to evaluate the residual power of the treatments, the theologines were counted on the animals on days 0, 7, 14, 21, 28, 35 and 42 post treatment. A completely randomized design was used and the study showed that Tukey p <0.05 difference between T2 and other treatments, the difference remained until the end of the investigation (week six): T1: 52. 13%, T2: 32.69%, T3: 58.97% and T4: 60.04%. To determine the reproductive efficiency, 2gr of theologines were collected from each animal, these were placed in Petri dishes and incubated. The eggs were weighed and incubated to verify the percentage of hatching and subsequently the efficacy on reproduction of Boophilus microplus. It was found that T3 and T4 achieved 0% reproductive efficiency in the theologies, while in the other two treatments they were reproduced in only 1.35% for T1 and 3.53% for T2. The T3 had a better development in terms of benefit - cost with a value of 0.05 $ to treat 10kg / pv.